2022
DOI: 10.1088/1755-1315/1060/1/012062
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fenugreek Seeds Gum on Quality of Pan Bread During Storage

Abstract: This search was conducted to extract the gum from fenugreek seed and studying the effects on bread staling, and its application a gum in controlling bread staling by replacing 0.5,0.75.1.1.5 and 2% wheat flour. Bread staling was measured under different storage conditions,. loaves were stored in polyethylene bag for 1,5and 7 days and temperature 25-30,4 and 18- C°, two techniques were used to study bread staling such Differential Scanning Calorimetry and Scanning Electron Microscopic, the moisture concent in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The only disadvantage is that it hydrates slowly because of the absence of an electrostatic change [88]. In the study by Al-Shammari et al [136], fenugreek seed gum was added to the storage of bread, and the results showed that this gum had lower staling, improved the bread quality, and increased the softness of crumb bread. No result has been found in the bibliography of its application in grapes or its by-products.…”
Section: Polysaccharidesmentioning
confidence: 99%
“…The only disadvantage is that it hydrates slowly because of the absence of an electrostatic change [88]. In the study by Al-Shammari et al [136], fenugreek seed gum was added to the storage of bread, and the results showed that this gum had lower staling, improved the bread quality, and increased the softness of crumb bread. No result has been found in the bibliography of its application in grapes or its by-products.…”
Section: Polysaccharidesmentioning
confidence: 99%
“…When fenugreek gum is added in different types of bakery products, it can retard staling in some foods like gluten‐free rice cake by lowering the retro‐gradation enthalpy and weight loss. Similarly, it also slows down staling in flat bread at refrigerated temperature or room temperature via controlling starch retrogradation (Al‐Shammari et al, 2022; Huang et al, 2016).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The water extract from germinated seeds was used in wheat flour biscuits to increase the chemical and sensory attributes and to hinder degenerative diseases (El-Naggar, 2019).Al-Shammari et al reported that the addition of fenugreek gums in cakes and biscuits can potentially improve the dough machinability making it soft enough to leave the mold pans easily and fine slicing without breaking crumbs. Moreover, a 1% fenugreek addition in butter prepared for batter produced the required film developing and binding characteristics that reduced the fats' and oils' absorption and penetration into doughnuts(Al- Shammari et al, 2022).…”
mentioning
confidence: 99%